A Community-Based Health Literacy Intervention to Improve Health Literacy, Health Behavior Self-Efficacy, and Quality of Life Among Older Adults With Frailty: A Quasi-Experimental Study - Juan Fang; Lihui Li; Xinfang Xie; Jinlan Yao (Journal of Gerontological Nursing, 2026)
Purpose: To investigate the effectiveness of a health education program on health literacy based on Wellness Motivation Theory (WMT) among frail older adults. Method: The current quasi-experimental study was conducted from September 2024 to January 2025 across two communities in Huzhou, Zhejiang Province, China. Participants aged 60 to 85 years with physical frailty were recruited, screened, and randomly assigned to an intervention ( n = 35) or control ( n = 35) group. The intervention included a 12-week program with 12 supervised online and offline sessions based on WMT. Data were collected at baseline and postintervention to assess health literacy, health behavior self-efficacy, and quality of life. Results: When compared to the control group, the intervention group demonstrated a significant improvement in all health literacy domains (all p = .001); health behavior self-efficacy for nutrition ( p = .018), psychological comfort ( p = .010), and exercise ( p = .001); and Mental Component Summary for quality of life ( p = .030). Conclusion: Findings suggest that a health education program based on WMT effectively enhances health literacy, health behavior self-efficacy, and quality of life in frail older adults.